Emotional intelligence and stress among nursing student, University Malaysia Sabah (UMS) - Norkiah Arsat; Norsimah Dasan; Sitti Nohaya Tawakal; Flora Bianus; NurNadia Syamira Zulkifli; Joy Pereirra Castella Peter (Malaysian Journal of Medicine and Health Sciences, 2020)
Most nursing students experience stress in nursing-related learning where they have to adapt to different teaching styles and clinical situations, to meet instructors’ expectations, work independently on learning objectives, and manage conflicts. In some aspects of academic requirement may be considered as highly stressful. Therefore, nursing students expected to have the ability to integrate emotional intelligence (EI) in their learning process. The aim of this study is to measure the level of EI and stress among UMS nursing students. Methods: A cross-sectional survey design using purposive sampling methods involving one hundred (100) nursing students. Trait EI Questionnaire-Short Form (TEIQue-SF) scale developed by Petrides & Furnham, (2006) and Jones Scoring Instrument: Students Nurse Stress Index (SNSI) scale developed by Jones and Johnston (1999) used to measure EI and stress level. Approval to conduct study obtained from Dean of faculty of Medicine and Health Sciences, UMS. Results: The data were analysed through descriptive method using SPSS for window 21.0. Total EI scores ranging from a low (M=2.41) to high (M=6.53) and Mean value 4.20, (SD + 0.705). Total high EI 62(62%). Total score for SNSI ranging from a low (M=1.5) to a high (M=4.18) and Mean value 2.92, (SD + 0.606). Total low stress 58(58%). Year 2 reported significantly high EI Mean value 4.24, (SD + 0.779) compared to the year 1 Mean value 4.22,(SD + 0.738), and Year 3, Mean value 4.15, (SD + 0.618). Year 1 reported significantly low stress Mean value 2.80, (SD + 0.598) compared to the Year 2, Mean value 2.90, (SD + 0.656), and Year 3, Mean value 3.06, (SD + 0.547). Conclusion: The level of EI was high and Stress level was low. However, attention should be given to nursing students with low EI as well as to nursing students with high levels of stress.